An Assessment of The-asiatic Black Bear-human Conflicts in Kupwara District, Jammu & Kashmir, India - Sanwal, C. S.; Lone, Raheel Anwar (Indian Forester, 2012)
The survey focussed to assess the nature and extent of the human-Asiatic black bear (Ursus thibetanus) conflicts in the Kupwara district recorded 68 cases of human casualties by black bear reported during 2005 to 2011. Male casualties by black bear were more (60.29%) then females (39.70%). Maximum human casualties (23.53%) were recorded during 2010 to 2011, showing increasing trend in human-black bear conflicts. Average data during 2005 to 2011 revealed marked monthly occurrence of attacks with highest in August (26.47%) followed by July (13.23%). Maximum cases of bear attacks on human occurred at crepuscular times (44.11%) in crop fields (51.47%). Drumming of empty tin or metal containers is the most commonly traditionally used protection measure, as 71% respondents reported using this technique. Recommendations include monitoring high conflict areas, public education and awareness to change the intolerant attitude of public towards black bear, etc. are some measures which may help to minimize the human- black bear conflicts.